Produksi Efipium Dafnia (Daphnia carinata King) dengan Pengaturan Fotoperiode dan Kepadatan Kultur - Irsyaphiani Insan; Chumaidi Chumaidi (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2006)
Daphnia carinata King is a planktonic crustacean commonly used as natural food for freshwater fish. This experiment was conducted to evaluate the effect of different culture densities of daphnids and photoperiod on the ephippia production. Daphnids of different densities, i.e. 15, 20, and 25 individuals per 20 ml water media were cultured in small bottles.  The bottles were placed in a refrigerator and treated with two different photoperiods, i.e. 10.5 light hours : 13.5 dark hours (10.5:13.5) and 4 light hours : 20 dark hours (4:20).  All refrigerators were set at 12° C.  The experiment was arranged in a Complete Randomized Design with factorial treatments (3x2) replicated six times. The ephippia were colleted from every bottle for 45 days. The results showed that the photoperiod of 10.5: 13.5 and daphnid densities of 25 individuals per 20 ml produced most ephippia (12.1). Different culture density within the same photoperiod had no significant effect on ephippia production.